2019
DOI: 10.1111/1753-0407.12986
|View full text |Cite
|
Sign up to set email alerts
|

Faecalibacterium prausnitzii‐derived microbial anti‐inflammatory molecule regulates intestinal integrity in diabetes mellitus mice via modulating tight junction protein expression

Abstract: Background Impaired intestinal barrier structure and function have been validated as an important pathogenic process in type 2 diabetes mellitus (T2DM). Gut dysbiosis is thought to be the critical factor in diabetic intestinal pathogenesis. As the most abundant commensal bacteria, Faecalibacterium prausnitzii (F. prausnitzii) play important roles in gut homeostasis. The microbial anti‐inflammatory molecule (MAM), an F. prausnitzii metabolite, has anti‐inflammatory potential in inflammatory bowel disease (IBD).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(88 citation statements)
references
References 43 publications
4
83
0
1
Order By: Relevance
“…We observed enrichment of disease-promoting pathogens, such as the family Enterobacteriaceae ( 30 ), in encephalitis patients. Conversely, some taxa that were depleted in the patient group, such as the genus Faecalibacterium , were previously believed to confer antiinflammatory benefits ( 31 ). These findings likely reflect numerous variables, including derangements in host physiology, multiple treatment exposures, and the presence of nosocomial pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…We observed enrichment of disease-promoting pathogens, such as the family Enterobacteriaceae ( 30 ), in encephalitis patients. Conversely, some taxa that were depleted in the patient group, such as the genus Faecalibacterium , were previously believed to confer antiinflammatory benefits ( 31 ). These findings likely reflect numerous variables, including derangements in host physiology, multiple treatment exposures, and the presence of nosocomial pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the reversal of hyperglycemia, conditional deletion of GLUT2 from the IECs and inhibition of glucose metabolism will fix the barrier dysfunction and prevent the spread of bacteria (76). Xu et al have shown that Faecalibacterium prausnitzii, one of the most frequent commensal bacteria in normal individuals with essential roles in gut homeostasis, generates anti-inflammatory molecules that enhance the expression of tight junctions and improve intestinal integrity during diabetes (77). However, in some cases, gut microbiota dysbiosis or altered microbial composition of the intestines could induce T2DM and lead to its progression (78).…”
Section: Gastrointestinal Tract (Git)mentioning
confidence: 99%
“…Multiple lines of investigation have suggested that epithelial barrier dysfunction may result from the loss of beneficial species due to intestinal dysbiosis. In db/db mice that spontaneously develop type 2 diabetes, epithelial dysfunction is accompanied by underrepresentation of the major butyrate producer, Faecalibacterium prausnitzii (76). F. prausnitzii is also nearly absent from Crohn's disease-associated gut microbiota (63,77).…”
Section: Barrier Maintenance By Microbial Productsmentioning
confidence: 99%